Synthesis and Characterization 6-Hydroxy 4 Metheyl -5 -Phenyla Zo Coumarins with Divalent Transition Metal Ions - Dalal .M. Ibrahim; Juliana Jumal; Farah Wahida Harun (International Organization of Scientific Research, 2024)
Non-Indexed Publication